ip100803_elic_NominalForms_tubeso - Ирина Пайковна Кошкарёва (Туглакова); Олеся Ханина (Bernard Comrie, 2010)
О.Ханина собирает с И.П.Кошкаревой основные формы существительного глухочередующегося класса tubeso 'тряпка, одежда, ткань' (см. набор форм в NounInflection_tundra_ToDo2010.doc) O.Khanina collects with I.P.Koshkarjova main forms of a devoiced alternating noun tubeso 'cloth(es)' (see the list of forms in NounInflection_tundra_ToDo2010.doc) Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title ip100803_elic_NominalForms_tubeso